THE INFLUENCE SERVICES QUALITY, PROMOTION AND PHYSICAL EVIDENCE AGAINST CUSTOMER LOYALTY CV. FUNTASTIC TOUR AND TRAVEL - SATRIA AJI GUMELAR; Saparduddin Mukhtar (Faculty of Economics, State University of Jakarta., 2014)
The purpose of this study is to find the influence of quality services, promotion and physical evidence of customer loyalty on CV. Funtastic Tour and Travel. Analysis method of research used quantitative analysis to compute multiple linear regressions by using the Statistical Program for Social Science (SPSS) 20 conducted on customers CV. Funtastic Tour and Travel. The results of this study indicated that the independent variable (quality of services, promotion and physical evidence were able to explain the variations that occurred on customer loyalty by 60, 2%. And explained that the variable of quality service did not affect the customer loyalty with a regression coefficient - 0,114, while the promotion variable affected positively to the customer loyalty with regression coefficients 0,274 and most dominant variable influenced positively customer loyalty is variable physical evidence of regression coefficients 0,588. Key word: service quality, promotion, physical evidence and customer loyalty